Extracting the -[function]2(1270) coupling in the [rho][rho]→[rho][rho]π+π− reaction through the angular distribution of the pions - Lebiedowicz, Piotr; Nachtmann, Otto; Szczurek, Antoni (Physical review, 2020)
We discuss how to extract the Pomeron-Pomeron-f2(1270) [PPf2(1270)] coupling within the tensor-Pomeron model. The general PPf2(1270) coupling is a combination of seven basic couplings (tensorial structures). To study these tensorial structures, we propose to measure the central-exclusive production of a π+π− pair in the invariant mass region of the f2(1270) meson. An analysis of angular distributions in the π+π− rest system, using the Collins-Soper and the Gottfried-Jackson frames, turns out to be particularly relevant for our purpose. For both frames, the cosθπ+ and ϕπ+ distributions are discussed. We find that the azimuthal angle distributions in these frames are fairly sensitive to the choice of the PPf2 coupling. We show results for the resonance case alone as well as when the dipion continuum is included. We show the influence of the experimental cuts on the angular distributions in the context of dedicated experimental studies at RHIC and LHC energies. Absorption corrections are included for our final distributions.
Im Titel ist "function" als mathematisches Zeichen dargestellt
Im Titel ist "rho" als griechischer Buchstaben dargestellt
Im Titel ist die Zahl "2" bei function tiefgestellt
Im Titel ist das Plus und Minus bei pi hochgestellt
Gesehen am 26.03.2020